A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae) - Ferraris, Jr., Carl J. (Zootaxa, 2004)
The species Clupisoma roosae, new species, is recorded from the upper Irrawaddy River, Myanmar. This species can be distinguished from its sole congener in Myanmar, Clupisoma prateri Hora, 1937, in having a shorter pectoral-fin spine that does not extend past the pelvic-fin origin, a reduced abdominal keel that extends anteriorly only to the level of the pelvic-fin base, only 11 pectoral-fin rays and 45 to 47 branched anal-fin rays. Although the two species occur in the Irrawaddy River, they have not been collected together and appear to inhabit different portions of the river basin. Clupisoma prateri is distributed in the lower and middle reaches of the Irrawaddy River as well as the nearby Sittang, Bago, and Salween rivers, while C. roosae appears to be restricted to the upper reaches of the Irrawaddy. To facilitate comparisons between the two species of Clupisoma in Myanmar, C. prateri is redescribed.